2015
DOI: 10.1021/acsnano.5b02021
|View full text |Cite
|
Sign up to set email alerts
|

Cu Nanoparticles Have Different Impacts in Escherichia coli and Lactobacillus brevis than Their Microsized and Ionic Analogues

Abstract: Copper formulations have been used for decades for antimicrobial and antifouling applications. With the development of nano-formulations of copper that are more effective than their ionic and micron-sized analogs, a key regulatory question is whether these materials should be treated as new or existing materials. To address this issue, here we compare the magnitude and mechanisms of toxicity of a series of Cu species (at concentration ranging from 2–250 µg/mL), including nano Cu, nano CuO, nano Cu(OH)2 (CuPro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
98
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 44 publications
(100 reference statements)
4
98
4
1
Order By: Relevance
“…Although L. brevis showed similar trends, there was a stronger response to the Cu NPs and significant (p < 0.05) membrane damage from exposure to both nCu(OH) 2 and the copper salts (Kaweeteerawat et al, 2015). Exposure to Cu NPs resulted in oxidative stress (measured by biotic reactive oxygen species (ROS) generation) for E. coli and L. brevis, but there was no effect from CuCl 2 , CuSO 4 , μCu or μCuO at the concentrations studied ([Cu] up to 250 mg/L) (Kaweeteerawat et al, 2015). These results are in line with previous work indicating that exposure to Cu NPs caused cellular oxidative stress in bacterial cells (Li et al, 2013), yeast cells (Kasemets et al, 2013), and mammalian cells (Liu et al, 2014).…”
Section: High Throughput/content Screening Studiesmentioning
confidence: 79%
See 4 more Smart Citations
“…Although L. brevis showed similar trends, there was a stronger response to the Cu NPs and significant (p < 0.05) membrane damage from exposure to both nCu(OH) 2 and the copper salts (Kaweeteerawat et al, 2015). Exposure to Cu NPs resulted in oxidative stress (measured by biotic reactive oxygen species (ROS) generation) for E. coli and L. brevis, but there was no effect from CuCl 2 , CuSO 4 , μCu or μCuO at the concentrations studied ([Cu] up to 250 mg/L) (Kaweeteerawat et al, 2015). These results are in line with previous work indicating that exposure to Cu NPs caused cellular oxidative stress in bacterial cells (Li et al, 2013), yeast cells (Kasemets et al, 2013), and mammalian cells (Liu et al, 2014).…”
Section: High Throughput/content Screening Studiesmentioning
confidence: 79%
“…Commercial Cu nanopesticides were less toxic than nCu and nCuO, and toxicity was lowest for micron-scale Cu particles. Sub-lethal effect assays qualitatively measuring membrane potential, membrane damage, cellular ROS generation, and electron transport activity revealed that Cu ions and nanosized Cu resulted in significant (p < 0.05) membrane damage and a decrease in electron transport activity in E. coli, while micron sized particles had no effect (Kaweeteerawat et al, 2015). Although L. brevis showed similar trends, there was a stronger response to the Cu NPs and significant (p < 0.05) membrane damage from exposure to both nCu(OH) 2 and the copper salts (Kaweeteerawat et al, 2015).…”
Section: High Throughput/content Screening Studiesmentioning
confidence: 98%
See 3 more Smart Citations